Ответ: 1) 1
[tex]2 \frac{1}{6} x - 3 \frac{3}{4} = 4 \frac{1}{6} x - 5 \frac{3}{4} x \\ 2 \frac{1}{6} x - 4 \frac{1}{6} x + 5 \frac{3}{4} x = 3 \frac{3}{4} \\ - 2x + 5 \frac{3}{4} x = 3 \frac{3}{4} \\ 3 \frac{3}{4} x = 3 \frac{3}{4} \\ x = 3 \frac{3}{4} \div 3 \frac{3}{4} \\ x = 1[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: 1) 1
[tex]2 \frac{1}{6} x - 3 \frac{3}{4} = 4 \frac{1}{6} x - 5 \frac{3}{4} x \\ 2 \frac{1}{6} x - 4 \frac{1}{6} x + 5 \frac{3}{4} x = 3 \frac{3}{4} \\ - 2x + 5 \frac{3}{4} x = 3 \frac{3}{4} \\ 3 \frac{3}{4} x = 3 \frac{3}{4} \\ x = 3 \frac{3}{4} \div 3 \frac{3}{4} \\ x = 1[/tex]